Legal Opinion: Peracunan Eks Spionase Rusia - Soeliongan, Amanda Eugenia (CV Rewang Rencang, 2020)
The poisoning of Sergei Skripal in Britain by Russian military intelligence drew a lot of criticism from various countries in the world. This action violates state sovereignty and violates international law because the assassination attempt used chemical weapons, namely a neurotoxin from the Soviet-era called Novichok. Britain finally gave a strong response by designating 23 Russian ambassadors as Persona Non-Grata, which was in accordance with the provisions of the 1961 Vienna Convention on Diplomatic Relations. Persona Non-Grata is the exclusive right of every country that can be used as a sanction if there is a violation of international law, although there can be arbitrariness in its use because the Recipient Country is not obliged to provide valid reasons. Therefore, Persona Non-Grata in diplomatic law can be used as a warning or a means of interrupting a diplomatic relationship that is considered incompatible. This paper will discuss the incident in terms of Diplomatic and Consular International Law.